Development of hepatocellular carcinoma in chronic hepatitis B patients with advanced fibrosis is independent of viral genotype. Issue 5 (9th November 2016) - Kumar, Rajneesh; Testoni, Barbara; Fresquet, Judith; Lim, Tony Kiat Hon; Hao, Ying; Tan, Hui Hui; Chow, Wan Cheng; Zoulim, Fabien
Abstract : Hepatitis B is leading cause of liver related morbidity in Asia with predominant genotypes B and C in East‐Asia. Data on Serum, intrahepatic viral‐markers, and long‐term follow‐up of prevalent genotypes (GT) B and C in patients with biopsy proven advanced fibrosis are sparse. To compare serum, intrahepatic viral‐markers and development of hepatocellular carcinoma (HCC) in GT‐B and C in patients with advanced fibrosis (Ishak ≥ 4). Sixty‐three treatment‐naïve patients identified with advanced fibrosis on liver‐biopsy performed between 1998 and 2000 at Singapore General Hospital. FFPE tissue was available for 59 patients and serum for 42 patients. HBV‐DNA was quantified in serum and liver while qHBsAg quantified in serum. Patients were followed‐up till December 2015. The median age was 47 ± 16 years, with 77.7% males. About 19 were GT‐B, 43 patients were GT‐C, and 1 had both GT‐B and C. Mean follow‐up was 13.5 years. The median serum HBV‐DNA was 6.25 ± 2.17 and 6.58 ± 1.85 log IU/ml, serum HBsAg was 3.29 ± 0.80 and 3.45 ± 1.85 log IU/ml, and intrahepatic HBV‐DNA was 0.52 ± 3.73 copies/cell and 0.4 ± 1.37 copies/cell in the GT‐B and C, respectively ( P  > 0.1 in all). Complete cirrhosis (Ishak‐6) was present in 47.6%, Ishak‐5 fibrosis in 33.3%, and Ishak‐4 fibrosis in 19% at recruitment. On follow‐up HCC developed in 8/43 in GT‐C and in 3/19 GT‐B ( P  = 0.86). Advanced age and cirrhosis were significant factors for development of HCC. No difference in serum HBV‐DNA, qHBsAg or intrahepatic HBV‐DNA was seen in the two genotypes. HCC development seen over long‐term follow‐up was independent of genotypes in patients with advanced fibrosis. J. Med. Virol. 89:845–848, 2017 . © 2016 Wiley Periodicals, Inc.